Pengaruh Leverage dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi: Studi pada Perusahaan Sektor Industri di Bursa Efek Indonesia Periode 2020–2023 - Anjeli Melita Br Aritonang; Eli Safrida; Jojor Lisbet Sibarani (Politeknik Ganesha Medan, 2025)
This study examines the effect of leverage and firm size on firm value and investigates the moderating role of profitability in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative approach with a causal associative design was employed, using 72 observations from 18 firms selected through purposive sampling. Data were obtained from annual financial statements and analyzed with Moderated Regression Analysis (MRA) using SPSS 27. The findings reveal that leverage and firm size do not significantly influence firm value, indicating that higher debt ratios or larger firm size alone do not enhance investor perceptions. However, profitability strengthens the relationship between leverage and firm value, while no moderating effect is observed in the link between firm size and firm value. These results contribute to financial literature by reaffirming the importance of profitability as a strategic factor in capital structure decisions. Practically, managers are encouraged to maintain strong profitability to ensure that debt financing strategies are positively perceived by investors and support value creation.